NURSE CARING BEHAVIORS AND PATIENTS’ LENGTH OF STAY: CORRELATIONAL STUDY - Ayu Dewi Nastiti (UNEJ e-Proceeding, 2020)
Background: Nursing is a profession that emphasizes an attitude of care and affection for patients. Nursing puts forward an understanding of human behavior and responses to health problems, how to respond to others, as well as understanding the advantages and disadvantages of patients. This study aims was to correlate the nurse's Caring behavior with the length of stay in the Inpatient Installation of Dr.R.Soedarsono General Hospital, Pasuruan City. Method: This research used the correlational descriptive method. The number of samples were 37 nurses. Variable In this research were nurse's Caring behavior and the length of stay. The data obtained will be analyzed used Rank Spearman Results: The results of Spearman Rank analysis show there was relationship between a nurse caring in nursing services with length of stay. It was shown with a significant 0.009 with a positive relationship direction of 0.501 so that it showed a relationship with a moderate category between the relationship of caring nurses in nursing services with length of stay. Discussion: The conclusion of this study there was a relationship between nurses caring behaviors and a length of stay. Based on this research it is recommended that Hospital continue to improve caring ability for professional nurses with skills training about caring behavior. Keywords: Caring, nursing services. length of stay